SARS-CoV-2 Variants of Concern and Variants of Interest Receptor Binding Domain Mutations and Virus Infectivity - Liu, Haolin; Wei, Pengcheng; Kappler, John W.; Marrack, Philippa; Zhang, Gongyi (Frontiers in Immunology, 2022)
The SARS-CoV-2 pandemic has lasted more than two years with over 260 million infections and 5 million deaths worldwide as of November 2021. To combat the virus, monoclonal antibodies blocking the virus binding to human receptor, the angiotensin converting enzyme 2 (ACE2), have been approved to treat infected patients. Inactivated whole virus or the full-length virus spike encoding adenovirus or mRNA vaccines are being used to immunize the public. However, SARS-CoV-2 variants are emerging. These, to some extent, escape neutralization by the therapeutic antibodies and vaccine induced immunity. Thus breakthrough infections by SARS-CoV-2 variants have been reported in previously virus infected or fully vaccinated individuals. The receptor binding domain (RBD) of the virus spike protein reacts with the host ACE2, leading to the entry of the virus into the cell, but spike is also the major antigenic site of the virus, with more than 90% of broadly neutralizing antibodies from either infected patients or vaccinated individuals targeting the spike RBD. Therefore, mutations in the RBD region are effective ways for SARS-CoV-2 variants to gain infectivity and escape the immunity build up by the original vaccines or infections. In this review, we will focus on the impact of RBD mutations in SARS-CoV-2 variants of concern (VOC) and variants of interest (VOI) on ACE2 binding affinity and escape of serum antibody neutralization. We will also provide protein structure models to show how the VOC and VOI RBD mutations affect ACE2 binding and allow escape of the virus from the therapeutic antibody, Bamlanivimab.